Measuring perceptions of Muslim consumers toward income tax rebate over zakat on income in Malaysia - Al-Mamun, Abdullah; Haque, A. K. M. Ahasanul; Jan, Muhammad Tahir (Emerald Group Publishing Ltd., 2019)
Abstract Purpose – The purpose of this study is to explore the variables that affect Muslim consumers’ perception towardstaxrebateoverzakatonincomeinMalaysia. Design/methodology/approach – A close-ended structured questionnaire was developed and a total numberof236validresponseswerecollectedthroughonlinesurveyfromtheMuslimsresidinginMalaysia. Findings – Thisstudyfoundthathalal-haramaspectofIslamicShariah,legalconsciousnessandreligiosity of Muslim consumers are positive signiﬁcant factors for growing perceptions towards tax rebate over zakat onincomeinMalaysia. Research limitations/implications – This study will deﬁnitely play an important leading role for the policy-makersandacademiciansinunderstandingtheperceptionsofMuslimconsumers. Practicalimplications – ThisstudycanassistzakatandtaxauthoritiesinMalaysiafortakingcorrective actionstoadaptorimprovethecurrentpolicyonthebasisofitsMuslimconsumers’perception. Social implications – The ﬁndings of this study can reduce the gap of understanding among Muslims in thesocietybylettingotherpeople’sperceptionstowardstaxrebatethroughzakatsysteminMalaysia. Originality/value – As there are not enough studies in this area, this study will deﬁnitely play an important leading role for the countries or policy-makers or concerned zakat or tax institutions all over the world in capitalizing the practices which is highly and positively perceived by the Muslim consumers in Malaysia.